Interaction of Antibiotics with Innate Host Defense Factors against Salmonella enterica Serotype Newport - George Sakoulas (American Society for Microbiology, 2017)
ABSTRACT This study examines the pharmacodynamics of antimicrobials that are used to treat Salmonella with each other and with key components of the innate immune system. Antimicrobial synergy was assessed using time-kill and checkerboard assays. Antimicrobial interactions with innate immunity were studied by employing cathelicidin LL-37, whole-blood, and neutrophil killing assays. Ceftriaxone and ciprofloxacin were found to be synergistic in vitro against Salmonella enterica serotype Newport. Ceftriaxone, ciprofloxacin, and azithromycin each demonstrated synergy with the human cathelicidin defense peptide LL-37 in killing Salmonella. Exposure of Salmonella to sub-MICs of ceftriaxone resulted in enhanced susceptibility to LL-37, whole blood, and neutrophil killing. The activity of antibiotics in vivo against Salmonella may be underestimated in bacteriologic media lacking components of innate immunity. The pharmacodynamic interactions of antibiotics used to treat Salmonella with each other and with components of innate immunity warrant further study in light of recent findings showing in vivo selection of antimicrobial resistance by single agents in this pathogen. IMPORTANCE It is becoming increasingly understood that the current paradigms of in vitro antimicrobial susceptibility testing may have significant shortcomings in predicting activity in vivo. This study evaluated the activity of several antibiotics alone and in combination against clinical isolates of Salmonella enterica serotype Newport (meningitis case) utilizing both conventional and physiological media. In addition, the interactions of these antibiotics with components of the innate immune system were evaluated. Azithromycin, which has performed quite well clinically despite high MICs in conventional media, was shown to be more active in physiological media and to enhance innate immune system killing. Alternatively, chloramphenicol did not show enhanced immune system killing, paralleling its inferior clinical performance to other antibiotics that have been used to treat Salmonella meningitis. These findings are important additions to the building understanding of current in vitro antimicrobial assay limitations that hopefully will amount to future improvements in these assays to better predict clinical efficacy and activity in vivo.